Linking Farmers to Markets: the Case of Zero Star Uni Pessoal - Correia, Vincente; Rola-Rubzen, Maria Fay (International Society of Horticultural Science, 2011)
This paper presents a case study of how linkages between horticulture farmers and markets are being developed in Timor Leste, focussing on the case of Zero Star Uni Pessoal. As an approach to poverty alleviation, an international aid agency initiated a private sector development program. Apart from helping farmers increase agricultural production, private sector involvement was encouraged. By strengthening the linkages between Zero Star and farmers, farmers benefited in terms of increasing incomes. Buyers also benefitted in terms of improvements in quantity and quality of the product, and therefore higher returns from trading.